Literature Review: Gambaran Monitoring Kedalaman Anestesi Pada Anestesi Umum - An An Farida; Roro Lintang Suryani; Made Suandika (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
The term "depth of anesthesia" refers to the extent to which a general anesthetic agent anesthetizes the central nervous system with a specific concentration of force at the time the drug is administered. The depth level of anesthesia plays an important role in determining surgical complications, and it is very important to keep the depth level of anesthesia under control for the operation to be successful. The purpose of this study is to determine the Monitoring Picture of Anesthesia Depth in General Anesthesia. The literature search will be conducted between 2018 and 2023. The methodof journals and scientific articles contained in this study are national and international journals that have been accounted for their validity. Sources of information obtained from databases are Google Scholar, Science Direct, and PubMed. Anesthesia depth monitoring with the most popular modern technique in practice is the Bixpectral Index Score (BIS) monitor. Anesthesia depth monitoring using BIS is more accurate than traditional anesthesia depth monitoring. Objective assessment of the depth of sedation can use the BIS tool that provides the best prediction of the patient’s degree of consciousness to] prevent the patient from waking up and remember actions, drug additions, and wake predictions more accurately by looking at changes in brain electrical activity depicted through EEG